(untitled) (The Pakistan Development Review, 2009)
This study investigates the econometrically empirical evidence of both the short-run and long-run interrelationships among human development, exports and economic growth in an ARDL framework for Pakistan. This study also examines causal linkages among the said variables by applying the Augmented Granger Causality test of Toda-Yamamoto (1995). By using data on Pakistan’s real GDP, real exports and Human Development Index (HDI) for the period 1970-71 to 2008-09, three models have been estimated. The results show cointegration between economic growth, physical capital, real exports and human development when human development is taken as dependent variables. Furthermore, unidirectional Granger causality running from real GDP to real exports has been found in Bivariate, Trivariate and Tetravariate causality framework. The inclusion of HDI as a measure of human development reduces the physical capital share in real GDP whereas it improves the robustness of the regression model. Real GDP seems to provide resources to improve human development in only the long-run while human capital accumulation does not seem to accelerate real GDP both in the short-run and the long-run. The empirical results of the study do not support ‘export-led growth hypothesis’ and human capital-based endogenous growth theory in case of Pakistan, however, it does support ‘growth-driven exports hypothesis’ in case of Pakistan. JEL classification: O11 Keywords: Human Development, Exports, Economic Growth, ARDL, Causality